Consumption of atmospheric methane by the Qinghai–Tibet Plateau alpine steppe ecosystem - H. Yun; Q. Wu; Q. Zhuang; A. Chen; T. Yu; Z. Lyu; Y. Yang; H. Jin; G. Liu; Y. Qu; L. Liu (The Cryosphere, 2018)
The methane (CH4) cycle on the Qinghai–Tibet Plateau (QTP), the world's largest high-elevation permafrost region, is sensitive to climate change and subsequent freezing and thawing dynamics. Yet, its magnitudes, patterns, and environmental controls are still poorly understood. Here, we report results from five continuous year-round CH4 observations from a typical alpine steppe ecosystem in the QTP permafrost region. Our results suggest that the QTP permafrost region was a CH4 sink of −0.86±0.23 g CH4-C m−2 yr−1 over 2012–2016, a rate higher than that of many other permafrost areas, such as the Arctic tundra in northern Greenland, Alaska, and western Siberia. Soil temperature and soil water content were dominant factors controlling CH4 fluxes; however, their correlations changed with soil depths due to freezing and thawing dynamics. This region was a net CH4 sink in autumn, but a net source in spring, despite both seasons experiencing similar top soil thawing and freezing dynamics. The opposite CH4 source–sink function in spring versus in autumn was likely caused by the respective seasons' specialized freezing and thawing processes, which modified the vertical distribution of soil layers that are highly mixed in autumn, but not in spring. Furthermore, the traditional definition of four seasons failed to capture the pattern of the annual CH4 cycle. We developed a new seasonal division method based on soil temperature, bacterial activity, and permafrost active layer thickness, which significantly improved the modeling of the annual CH4 cycle. Collectively, our findings highlight the critical role of fine-scale climate freezing and thawing dynamics in driving permafrost CH4 dynamics, which needs to be better monitored and modeled in Earth system models.